An analytic study of the fractional order model of HIV-1 virus and CD4+ T-cells using adomian method - Kamel Al-Khaled; Maha Yousef (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this article, we study the fractional mathematical model of HIV-1 infection of CD4+ T-cells, by studying a system of fractional differential equations of first order with some initial conditions, we study the changing effect of many parameters. The fractional derivative is described in the caputo sense. The adomian decomposition method (Shortly, ADM) method was used to calculate an approximate solution for the system under study. The nonlinear term is dealt with the help of adomian polynomials. Numerical results are presented with graphical justifications to show the accuracy of the proposed methods.